Advanced interior mediastinal yolk sac tumor with superior vena cava syndrome (SVCS) - Zainulabid, Ummu Afeera; Abdul Razak, Megat Razeem; How, Soon Hin; Ibrahim, Aishah; Harun, Norra; Mohamed, Dahlia (2019)
ntroduction Mediastinal germ cells tumors are extragonadal germ cell tumors (EGGCTs). They are more common in men. It is an extremely rare tumor and it has a worse prognosis than gonadal germ cell tumors.